Preparation method and application of Co-Ni-C-based high-temperature alloy material
The preparation method for Co-Ni-C high-temperature alloys addresses mechanical and oxidation resistance issues by optimizing element ratios and using TiC to enhance γ′ phase stability, resulting in improved mechanical properties and oxidation resistance.
Patent Information
- Application Number
- CN202510460247.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-15
AI Technical Summary
The existing Co-Ni-based high-temperature alloys have shortcomings in terms of mechanical properties and high-temperature oxidation resistance. It is difficult to find a suitable alloy ratio to combine γ′ dissolution temperature, γ′ phase volume fraction, γ′ phase stability, high-temperature oxidation resistance and high-temperature mechanical properties.
TiC is used as an intermetallic compound to introduce C element, and through fine smelting and heat treatment processes, Co-Ni-C-based high-temperature alloy is prepared to ensure accurate alloy composition and form a uniform γ/γ′ co-uniform phase, improving the hardness and oxidation resistance of the alloy.
The mechanical properties and high-temperature oxidation resistance of Co-Al-V system high-temperature alloys are improved, and the alloy structure is refined and the oxidation resistance is improved. It is suitable for high-temperature working parts in the aerospace field.
Smart Images

Figure CN120311065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of superalloy materials, and in particular to a preparation method and application of a Co-Ni-C-based superalloy material. Background Art
[0002] In the research of new superalloy systems, the regulating effect of nickel element on the microstructure of materials has been widely verified. Experimental data show that nickel, as a key alloying element, can effectively enhance the stability of the γ'-strengthening phase, not only significantly increasing the dissolution temperature threshold of this phase in cobalt-based alloys, but also expanding the coexistence composition range of the γ and γ' phases. It is worth noting that in the classical cobalt-based alloy system, it is usually necessary to maintain a nickel content of 20-30 at% to ensure the structural stability of the face-centered cubic structure γ-Co at high temperatures, and this composition design can effectively prevent the occurrence of harmful phase transformations. In terms of functional characteristics, the B. Gao team systematically studied and revealed the unique influence mechanism of nickel element on oxidation kinetics. By increasing the concentration gradient of Cr3+ in the surface oxide layer, it significantly accelerates the dynamic formation process of the dense Cr2O3 protective film. Based on these characteristic advantages, the modern alloy design concept tends to develop cobalt-based systems with high nickel content, and the extension of this technical path directly promotes the rapid development of Co-Ni-based superalloys. While maintaining the inherent advantages of cobalt-based materials, this type of alloy realizes the synchronous optimization of multiple performance indicators through the synergistic effect of nickel element, showing broad application prospects. Some scholars have reported that Ni element is a γ'-phase stabilizer, and its addition increases the γ'-phase solvus temperature of the new cobalt-based superalloy and broadens the γ / γ' two-phase composition region. In addition, traditional cobalt-based superalloys usually adopt a relatively high addition of Ni element (20 at%-30 at%) to inhibit the phase transformation of γ-Co (FCC structure). The addition of Ni element can also improve the high-temperature oxidation resistance of the alloy. B. Gao et al. studied the effect of Ni element content on the oxidation resistance of Co-based superalloys. The research shows that the addition of Ni element can increase the concentration of Cr3+, thus promoting the growth of Cr2O3. Therefore, in the design of cobalt-based superalloys, a high content of Ni element is necessary. Therefore, based on cobalt-based superalloys, Co-Ni-based superalloys have been vigorously studied by scholars due to their good comprehensive performance and great potential.
[0003] The new Co-Ni-based superalloy has a high melting point and good high-temperature stability, and has great application potential in aerospace turbine engines. Co-based superalloys have higher melting points and oxidation resistance, so Co-based superalloys and new Co-Ni-based superalloys have become the only way for the development of superalloys. At present, Co-Ni-based superalloys are still in the initial stage of research and development. Although more metal elements are added to the alloy, and the existing problems of the alloy are improved by changing the alloy elements and their proportions, it is still difficult to find a suitable alloy ratio to obtain γ′ dissolution temperature, γ′ phase volume fraction, γ′ phase stability, high-temperature oxidation resistance, and its most critical high-temperature mechanical properties.
[0004] At present, Co-Al-V system superalloys have attracted wide attention due to their good high-temperature mechanical properties and high specific strength. At present, Co-Ni-Al-V based superalloys are the alloys with low density and stable high-temperature structure among Co-based superalloys, but the mechanical properties and high-temperature oxidation resistance of the alloys need to be improved, and their high-temperature oxidation resistance mechanism is still unclear. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present invention provides a preparation method of a Co-Ni-C based high-temperature alloy material and its application, so as to improve the mechanical properties and high-temperature oxidation resistance of the Co-Al-V system high-temperature alloy.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A method for preparing a Co-Ni-C based high temperature alloy material comprises the following steps:
[0008] Step S1, preparing raw materials according to the ratio;
[0009] Step S2, except TiC, Co, and Ni, the remaining raw materials are placed in a smelting furnace in descending order of melting point for smelting, with the raw materials with the lowest melting point placed at the bottom, TiC placed at the bottom of all raw materials, and Co and Ni placed at the top; after smelting, an alloy ingot is obtained;
[0010] The powder in the raw materials is easy to cause splashing. Although TiC has a high melting point, it is placed at the bottom of all raw materials because it is a powder;
[0011] Step S3, the alloy ingot has a metallic luster, and a small amount of oxide layer is formed on the surface, which is light yellow; therefore, it needs to be polished to remove the oxide layer;
[0012] Step S4, encapsulating the alloy ingot into a quartz tube for heat treatment.
[0013] As a further improvement of the above technical solution:
[0014] Preferably, pre-treatment is carried out before using the granular or massive raw materials. The pre-treatment process is as follows:
[0015] S1-1, finely grind the surface of the material, remove surface impurities and various metal oxide layers, and load it into a beaker;
[0016] S1-2, add absolute ethanol to the beaker and perform ultrasonic cleaning for 5-10 min, repeat 3 times, and ensure that there are no impurities in the raw materials after cleaning;
[0017] S1-3, after cleaning, put the raw materials into a dryer to dry and remove the residual ethanol on the surface;
[0018] S1-4, store the powdered materials in the dried raw materials in kerosene.
[0019] Preferably, in step S2, the air in the melting furnace is evacuated to vacuum by a mechanical pump and a vacuum pump, the vacuum pump is closed, and argon is introduced by the mechanical pump to return the furnace cavity to normal pressure, and then the gas is recycled and washed to evacuate the air in the melting furnace to ensure that there is no interference from other gases except argon in the melting environment. Finally, vacuum melting is carried out in a high-purity argon atmosphere using a vacuum melting furnace.
[0020] Preferably, in step S4, the alloy ingot is loaded into a cylindrical alumina crucible, and then placed into a quartz tube, and the quartz tube is encapsulated with a high-temperature flame.
[0021] Preferably, before encapsulation, the inside of the quartz tube is evacuated to vacuum multiple times, and argon is introduced for gas washing to ensure that there is no oxygen in the quartz tube.
[0022] Preferably, in step S4, heat treatment is carried out in a muffle furnace: first, the alloy ingot in the quartz tube is heated to 1250 °C with the furnace and held for 10 h for homogenization annealing. After the holding time ends, the furnace is cooled to 850 °C for aging treatment, and the heat treatment time is 50 h to 100 h; after heat treatment, the quartz tube is taken out of the muffle furnace and directly subjected to water quenching treatment. When water quenching, the quartz tube should be broken to ensure that the sample contacts with water and is quickly cooled to obtain a high-temperature γ / γ′ phase coherent tissue structure.
[0023] Preferably, in step S1, the atomic percentages of the preparation raw materials are: Co 35-40%, Ni 25-35%, Al 8-15%, V 3-6%, Ta 2-5%, Ti 1-3%, Cr 10-14%, TiC 0.1-0.5%. Among them, the purities of Co, Ni, Al, V, Ta, Ti, and Cr are all 99.9%. Co, Ni, Al, Ta, Ti, and Cr are in granular or massive form, and the C element is introduced through the intermetallic compound TiC.
[0024] Preferably, the TiC has a particle size of 40 to 300 mesh. 300 mesh is preferred. The alloy carbide diffraction intensity prepared from 300-mesh TiC powder is higher. The performance of the alloy prepared from 300-mesh TiC powder can be judged to be better through the diffraction intensity.
[0025] Preferably, the Co-Ni-C based superalloy material includes an AlCrC2 phase and a γ / γ' coherent phase.
[0026] Preferably, C in the alloy is 0.3 at%. The alloy has the best oxidation resistance when C is 0.3 at%.
[0027] The present invention also provides an application of a Co-Ni-C based superalloy material prepared by the above preparation method. The Co-Ni-C based superalloy material is used as a high-temperature working component material in an aeroengine, a rocket engine, a gas turbine, a gasoline or diesel engine.
[0028] The preparation method and application of the Co-Ni-C based superalloy material provided by the present invention have the following advantages compared with the prior art:
[0029] For the preparation method and application of the Co-Ni-C based superalloy material of the present invention, an increase in the C element will improve the hardness of the alloy. The Laves phase dispersed at the grain boundaries after solution aging treatment of the alloy can improve the strength of the alloy. The C element refines the structure of the alloy and improves the mechanical properties.
[0030] For the preparation method and application of the Co-Ni-C based superalloy material of the present invention, the intermetallic compound TiC is used to introduce the C element. As an intermetallic compound, TiC is more likely to fuse with various refractory elements and there will be no loss of the C element, ensuring the accurate composition of the prepared alloy. Description of the Drawings
[0031] Figure 1 It is an image of the as-cast structure of the Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) alloy prepared from C powder in the comparative example under backscattered electron mode scanning of a scanning electron microscope.
[0032] Figure 2 It is the microstructure of the Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) based superalloy prepared from TiC in Example 1 under the backscattered mode.
[0033] Figure 3 It is the microstructure and element surface scan image of the Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(0.3) alloy matrix prepared from TiC in Example 2 under the backscattered mode.
[0034] Figure 4 It is the microstructure and elemental surface scan image in the backscattering mode at the uneven part of the matrix composition of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(0.5) alloy prepared in Example 3.
[0035] Figure 5 It is the cross-sectional morphology and surface scan data of the C(0.3) alloy oxidized at 1000 °C for 50 h in the application implementation of the present invention.
[0036] Figure 6 It is the Vickers hardness value of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) based superalloys with different compositions in the application implementation of the present invention. Specific embodiments
[0037] The following details the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only for the purpose of illustrating and explaining the present invention, and are not intended to limit the present invention.
[0038] The preparation method of the Co-Ni-C based superalloy material of the present invention, the original composition of the alloy is set as
[0039] Co-30Ni-10A1-5V-4Ta-2Ti-12Cr-C(x), where the amount of C powder added between each component is determined by controlling the amount of x. Through the conversion of atomic percentage to mass percentage, the mass ratio of each sample required in practice is obtained. The sample ratio is carried out according to Table 1. The purpose of using pure C to make samples is to compare whether there are differences between introducing carbon elements by C and TiC, and which way of introduction is better.
[0040] Table 1 Composition ratio of superalloy material (at.%)
[0041]
[0042]
[0043] The preparation is carried out according to the following method:
[0044] Step S1, prepare the raw materials according to the ratio, and obtain the mass ratio of each sample required in practice by converting the atomic percentage to the mass percentage (at%~wt%). Both V and C are powders and V is very easy to oxidize, so they are all stored in kerosene. The purpose of using pure C to make samples is to compare whether there is a difference between the introduction of carbon elements between C and TiC, and which method of introduction is better. Co, Ni, Al, Ta, Ti, and Cr materials are all particles or blocks. Before using the particles and block raw materials, it is necessary to grind the surface of the materials to remove surface impurities and various metal oxide layers, and then put them into a beaker, add enough anhydrous ethanol to the beaker for ultrasonic cleaning for 5-10 min, and repeat the cleaning 3 times to ensure that the raw materials are free of any impurities. Then put the raw materials into a dryer to dry, remove the surface ethanol residue, and prepare the dried raw materials through an electronic balance with an accuracy of 0.1mg. Since the powdered materials are stored in kerosene, no treatment is required.
[0045] Step S2, the melting points of the alloy components are different. In order to reduce the splashing and volatilization of low-melting-point elements, except TiC, Co, and Ni, the remaining raw materials are placed in the smelting furnace in order from high to low melting points for smelting, and the ones with low melting points are placed at the bottom. TiC or C is placed at the bottom of all raw materials. The Co and Ni materials in the raw materials are mostly block-shaped and have a high content. Co and Ni are placed at the top so that they can cover the elements below and play a certain protective role; the powder in the raw materials is easy to cause splashing. Although TiC has a high melting point, it is placed at the bottom of all raw materials because it is a powder.
[0046] The air in the furnace is evacuated to vacuum by mechanical pump and vacuum pump, the vacuum pump is turned off and sufficient argon is introduced into the mechanical pump to return the furnace chamber to normal pressure, and then the above steps are circulated and washed to evacuate the air in the smelting furnace, and ensure that there is no interference from other gases in the smelting environment except argon. Finally, a vacuum smelting furnace is used to prepare the smelting of samples in a high-purity argon atmosphere. During the preparation process, cooling water is continuously circulated in the joystick to prevent the arc from damaging the copper table. Before melting, a sufficient amount of high-purity Ti particles with an oxide layer treated should be placed in the central groove of the copper table. Its function is to absorb residual oxygen and other active gases as much as possible to ensure the stability of the smelting environment, so as to prevent other gases generated after melting the previous samples from contaminating subsequent samples, which is beneficial to improve the purity of the samples.
[0047] After adjusting the current, strike an arc to melt the sample. Each sample should be melted repeatedly more than 5 times. The melting current should be adjusted from low to high. Different compositions of samples have different configured currents. Try to ensure that the current increases slowly from low to high, which can prevent splashing and make the melted samples more uniform. When the sample starts to melt, the current adjustment should be stopped. Each melting time is about 1 min. After each melting, turn the sample over to ensure the uniformity of the internal composition of the alloy and prevent refractory substances from depositing at the bottom. The obtained alloy ingot is in the shape of a flat oval button, showing a metallic luster, but there may still be a small amount of oxide layer formed on the surface, which is light yellow. Therefore, it still needs to be polished to remove the oxide layer and then vacuum packaged.
[0048] Step S3: The obtained alloy ingot shows a metallic luster, and a small amount of oxide layer will be formed on the surface, which is light yellow; therefore, it needs to be polished to remove the oxide layer.
[0049] Step S4: Package the alloy ingot into a quartz tube for heat treatment. Conduct heat treatment in a muffle furnace: First, heat the alloy ingot in the quartz tube to 1250 °C with the furnace and hold for 10 h for homogenization annealing. After the holding time ends, cool with the furnace to 850 °C for aging treatment, and the heat treatment time is 50 h to 100 h; after heat treatment, take out the quartz tube from the muffle furnace and directly conduct water quenching treatment. When water quenching, break the quartz tube to ensure that the sample contacts with water and cools rapidly to obtain a high-temperature γ / γ′ phase coherent microstructure.
[0050] Example 1
[0051] Figure 2 It is an image of the as-cast microstructure of the Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) alloy prepared by TiC powder under the backscattered electron mode scanning of a scanning electron microscope after solution heat treatment at 1200 °C for 8 h and then cooling to 850 °C for aging treatment for 50 h. It can be seen that the dendritic structure of the alloy after solution treatment at 1250 °C completely disappears. The way of introducing C element by TiC powder completely avoids the problem of carbon element accumulation hindering dendritic dissolution. The TiC powder is more uniformly fused with other elemental metals, and the homogenization of the alloy matrix composition is improved. After the dendrites dissolve, the alloy matrix is uniform. As shown in (a) and (b) in the figure, the γ′ phase size has obvious refinement effects, and the average γ′ phase size is reduced to 100 - 200 nm. (c) and (d) in the figure are the non-uniform positions of the alloy. Among them, (c) is a Ta element-rich particle, where the white is Ta metal, and the middle black part is found to be TiC and Cr element by point scanning, judged to be a mixture of Cr23C6 and TiC. The Ta metal wraps the strengthening phase formed by the carbide. The two white pieces in (d) are Ti element-rich regions. The surrounding black phases are all various fine carbide phases, indicating that the influence of Ti element on the distribution of carbide phases is small and can be almost ignored.
[0052] Example 2
[0053] Figure 3 Images and elemental surface scan data distributions under the backscattered electron mode scan of a scanning electron microscope for the as-cast microstructure of a Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(0.3) alloy prepared with TiC powder after solution heat treatment at 1200 °C for 8 h and then aging treatment at 850 °C for 100 h. It can be seen from the scanning images that the method of introducing C element by TiC into this component alloy is very successful. Further confirmation based on the elemental surface scan data shows that the introduction of C element by TiC is very successful. In the elemental surface scan data, the distributions of three elements, Co, Ni, and V, are dense and uniform, and the distribution of C element is slightly sparse. However, compared with the alloy sample prepared with C powder, there is no element accumulation.
[0054] Example 3
[0055] Figure 4 Images and elemental surface scan data distributions under the backscattered electron mode scan of a scanning electron microscope for the non-uniform matrix composition in a Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(0.5) alloy prepared with TiC powder. The non-uniform composition positions appearing in the images under the backscattered electron mode scan are caused by the enrichment of Ta and Ti elements. The bright spot positions are due to the non-uniform melting of Ta and Ti elements. As high melting point metals, Ta and Ti are prone to segregation during the alloy melting process.
[0056] It can be seen from the elemental surface scan data in the figure that except for the enrichment of Ta element, Ti is not enriched in the black area at the center of the bright spot. Instead, the brightness of C element is very high in the central black area, indicating that this area is mainly Ta and its carbides. Moreover, the brightness of C element in other areas of the bright spot is also higher than that in the alloy matrix. Therefore, the entire non-uniform composition area does not have an adverse effect on the alloy matrix. The appearance of non-uniform composition can form more fine carbide phases under the introduction of C element, which has an enhancing effect on the alloy performance.
[0057] The present invention uses this intermetallic compound TiC to introduce C element. As an intermetallic compound, TiC is more easily fused with various refractory elements and there will be no loss of C element, ensuring the accurate composition of the prepared alloy. TiC has a high melting point, which is closer to the melting points of other refractory elements in the alloy. When fused, it can make the alloy composition more uniform.
[0058] Comparative Example
[0059] In the process of preparing alloys with C powder, the melting of samples is difficult, and there is serious loss during the introduction of C element, resulting in certain errors in the alloy composition. Moreover, in the alloy samples prepared with C powder in the early stage, not only uneven structures but also dendritic structures still exist in a network form after solution treatment and aging. These are all due to factors such as the easy volatilization and caking of carbon powder during the melting process.
[0060] Figure 1 It is the image of the as-cast microstructure of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) alloy prepared with C powder under the backscattered electron mode scanning of a scanning electron microscope. (a) Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-0.1C; (b) Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-0.3C; (c)(d) Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-0.5C. It can be seen that the alloys of each composition present dendritic morphologies. During the solidification process of the alloy, when the temperature drops to near the liquidus line, a uniform liquid phase is first formed. As solidification begins, refractory elements in the liquid phase form small crystal nuclei and serve as seeds to guide the growth of dendrites. Near the crystal nuclei, the dendritic phase grows by absorbing solutes from the liquid phase, forming a dendritic structure with a specific direction. The whole process is affected by factors such as alloy composition and solidification rate, presenting a complex and orderly solidification phenomenon. With the adjustment of the composition, the microstructure morphology changes to a certain extent. However, the main components of the dendrites are still the matrix elements Ni, Co, and Cr that make up the alloy. To make the dendrites in the as-cast alloy structure disappear and to see the strengthening γ′ phase more clearly by promoting composition homogenization, solution treatment and aging of the alloy are required.
[0061] Experimental verification of oxidation performance
[0062] Adding C element to the alloy, the C element can improve the oxidation resistance of the alloy at high temperatures. At the same time, it can perform solution strengthening on the γ′ phase and form C-containing oxides under high-temperature oxidation conditions, which are pinned in the oxide layer to make the oxide layer of the alloy have better anti-shedding ability. Moreover, the high-temperature oxidation performance of this new Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) based superalloy at 1000 °C has not been studied. Therefore, this invention studies the influence of C element content on the high-temperature oxidation performance and oxidation mechanism of the new Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) based superalloy at 1000 °C.
[0063] For C(0.1) and C(0.3) alloys, adding C improves oxidation resistance, which is particularly obvious in low-C alloys. The oxidation resistance of C(0.3) alloy is improved more compared to C(0.1) alloy, while it is not obvious in high-C alloys. At the same time, the addition of C continuously improves the oxidation resistance of the alloy. When the C element is added to 0.3 at%, the oxidation rate of the alloy reaches 5.56×10 - 8 g 2 cm -4 h -1 。
[0064] Table 2 shows the oxidation rates of each alloy obtained by fitting (K p )
[0065]
[0066] Table 2 lists the oxidation rates of each alloy obtained by fitting. The oxidation rates of C(0.1), C(0.3) and C(0.5) alloys are 2.34×10 -7 、5.56×10 -8 and 3.76×100 -7 g 2 cm -4 h -1 respectively. It can be seen that adding C has a positive effect on the oxidation behavior of superalloys at 1000°C, but too much C reduces the high-temperature oxidation resistance of superalloys at 1000°C.
[0067] Figure 5Cross-sectional morphology and surface scanning data of C(0.3) alloy oxidized at 1000 °C for 50 h. It can be observed that there is obvious stratification in the oxide layer on the alloy surface. In the figure, the oxide layer has grown to 38 μm. Compared with the initial stage of oxidation, the oxide film has not only become much thicker, but also cracks have appeared at the connection between the oxide layer and the bottom matrix. The cracks are thick and branched, and a small number of fine branches penetrate into the surface oxide film. In the middle stage of oxidation, as the oxide layer thickens, according to the surface scanning data, the main positions where stratification occurs are where the signals of Cr and Al elements are very strong. Combining the surface morphology and XRD data analysis, the inner-layer oxides are mainly formed by the complete oxidation of the outer-layer Co and Ni alloys. The continuous growth of (Co, Ni)O oxides on the surface results in gaps and holes, promoting the alloy oxidation to enter the inner layer. The Cr and Al in the inner layer begin to oxidize. It can be seen that the most severely stratified area in the inner layer is mainly Al2O4. Al2O4 adheres to the matrix through the upper oxide film, isolating the upper voids and preventing further oxidation of the alloy. Compared with the middle stage of oxidation, the amounts of Cr2O3, Al2O4, and Co3V2O in the oxide film continue to increase in the middle stage of oxidation. Among them, a large amount of Cr2O3 aggregates in the upper-layer oxides, and the growth of Co3V2O is stable and relatively uniform. Combining the XRD pattern of the alloy surface, it can be judged that the main components of the surface oxide film are Cr2O3, Al2O4, and Co3V2O. Among them, the amount of Cr2O3 is the largest, followed by Al2O4 and then Co3V2O. And there is segregation of Al2O4 in the figure. According to the distribution of Al in the surface scanning, it can be seen that Al2O4 mainly covers the junction between the matrix and the oxide film, and the surface oxides are a mixture of a large amount of Cr2O3 and Co3V2O.
[0068] Verification of mechanical property experiments
[0069] In order to study the effect of C element on the hardness of the alloy, Vickers microhardness experiments were carried out on the alloy after heat treatment. Figure 6 Hardness images of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr-C(x) based superalloys. Among them, when the C element is 0.1 at%, 0.3 at%, and 0.5 at% respectively, the micro-Vickers hardness of the alloy is 362.3, 432.4, and 410.9. The solid solution of C element into the alloy matrix can improve the hardness of the alloy. And as the content of C element increases, a large amount of Laves phase will precipitate in the alloy. The Laves phase is a brittle phase with high hardness and decreased toughness. However, the matrix of the alloy is a coherent double-FCC phase, which can improve extremely high plasticity and toughness. Therefore, the increase in hardness is beneficial.
[0070] In summary, the present invention preferably uses 0.3 at% of C element. The increase of C element will increase the hardness of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr alloy. When the addition amount of C element is 3 at%, the micro-Vickers hardness (HV) of the alloy is 432.4, and the compressive strength is 942 MPa. After solution aging treatment, the Laves phase dispersed at the grain boundaries can improve the strength of the alloy. In addition, the C element refines the microstructure of the alloy and improves the mechanical properties. With the increase of C, the oxidation resistance of Co-30Ni-10Al-5V-4Ta-2Ti-12Cr alloy increases at 1000 °C. When C is 0.3 at%, the oxidation resistance of the alloy is the best, and the oxidation rate is only 5.56×10 -8 g 2 cm -4 h -1 . At the initial stage of alloy oxidation, the oxides of Co and Ni are (Co, Ni)O. After a period of time, Al2O3, Cr2O3 and Co, Ni-based spinel oxides (CoAl2O4, NiAl2O4, etc.) appear inside the alloy.
[0071] The above-mentioned embodiments are only preferred embodiments of the present invention, and do not impose any form of limitation on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.
Claims
1. A preparation method of a Co-Ni-C-based superalloy material, characterized in that, The method for preparing the high temperature alloy material according to claim 1 comprises the following steps: Step S1, preparing raw materials according to the ratio; Step S2, except TiC, Co, and Ni, the remaining raw materials are placed in a smelting furnace in descending order of melting point for smelting, with the raw materials with the lowest melting point placed at the bottom, TiC placed at the bottom of all raw materials, and Co and Ni placed at the top; after smelting, an alloy ingot is obtained; Step S3, obtaining the alloy ingot and performing grinding and polishing to remove the oxide layer; Step S4, encapsulating the alloy ingot into a quartz tube for heat treatment.
2. The preparation method according to claim 2, wherein The granular or block raw materials are pretreated before use. The pretreatment process is as follows: S1-1, fine grinding the material surface, removing surface impurities and various metal oxide layers, and loading into a beaker; S1-2, add anhydrous ethanol to the beaker and perform ultrasonic cleaning for 5-10 minutes, repeat 3 times, and ensure that the raw materials are free of any impurities; S1-3, after cleaning, the raw material is placed in a dryer to dry and remove the ethanol residue on the surface; S1-4, storing the powdered material in the dried raw material in kerosene.
3. The preparation method according to claim 1, characterized in that, In the step S2, the air in the smelting furnace is evacuated to a vacuum, argon gas is introduced to return the furnace chamber to normal pressure, the gas is recirculated and washed, the air in the smelting furnace is evacuated, and finally a vacuum smelting furnace is used to carry out smelting preparation in a high-purity argon atmosphere.
4. The preparation method according to claim 1, wherein, In the step S4, the alloy ingot is placed into a cylindrical alumina crucible, which is then placed into a quartz tube, and the quartz tube is sealed with a high-temperature flame.
5. The preparation method according to claim 4, wherein Before packaging, the quartz tube is evacuated to a vacuum and purged with argon gas.
6. The preparation method according to claim 4, characterized in that, In the step S4, heat treatment is performed in a muffle furnace: first, the alloy ingot in the quartz tube is heated to 1250° C. with the furnace and kept warm for 10 hours, and homogenized annealing is performed. After the holding time, the alloy ingot is cooled to 850° C. with the furnace for aging treatment, and the heat treatment time is 50 hours to 100 hours. After the heat treatment, the quartz tube is taken out of the muffle furnace and directly water quenched. The quartz tube is broken during water quenching to ensure that the sample contacts water and cools quickly to obtain a high-temperature γ / γ′ phase coherent structure.
7. The preparation method according to claim 6, wherein In the step S1, the atomic percentages of the prepared raw materials are: Co 35-40%, Ni 25-35%, Al 8-15%, V 3-6%, Ta 2-5%, Ti 1-3%, Cr 10-14%, TiC 0.1-0.5%, wherein the purity of Co, Ni, Al, V, Ta, Ti, and Cr is 99.9%, Co, Ni, Al, Ta, Ti, and Cr are particles or blocks, and the C element is introduced through the intermetallic compound TiC.
8. The preparation method according to claim 7, wherein The TiC particle size is 40-300 meshes.
9. The preparation method according to claim 7, wherein The Co-Ni-C based high temperature alloy material comprises an AlCrC2 phase and a γ / γ′ coherent phase.
10. Use of a Co-Ni-C-based superalloy material prepared by the preparation method according to any one of claims 1-9, characterized in that: The Co-Ni-C-based high-temperature alloy material is used as a high-temperature working component material in aviation engines, rocket engines, gas turbines, gasoline or diesel engines.
Citation Information
Cited By
Heat treatment method for improving precipitation phases of different Ni-based alloy coatings
CN120924911A